Integrating Justice Constructs into the Turnover Process: A Test of a Referent Cognitions Model - Aquino, Karl; Griffeth, Rodger W.; Allen, David G.; Hom, Peter W. (Academy of Management Journal, 1997)
In the model tested, we posit that employees' outcome and supervisor satisfaction result from referent outcomes, justifications, and the likelihood of amelioration. These satisfaction facets are then related to turnover through withdrawal cognitions. Structural equation modeling was used to assess the fit of this model and alternatives. Although the original model had a good fit, a competing model provided a better one, with most hypothesized relationships supported. The implications of accepting the alternative model over the original are discussed.